Wearable High‐Density MXene‐Bioelectronics for Neuromuscular Diagnostics, Rehabilitation, and Assistive Technologies - Garg, Raghav; Driscoll, Nicolette; Shankar, Sneha; Hullfish, Todd; Anselmino, Eugenio; Iberite, Francesco; Averbeck, Spencer; Rana, Manini; Micera, Silvestro; Baxter, Josh R.; Vitale, Flavia (Small methods, 2023)
High‐density surface electromyography (HDsEMG) allows noninvasive muscle monitoring and disease diagnosis. Clinical translation of current HDsEMG technologies is hampered by cost, limited scalability, low usability, and minimal spatial coverage. Here, this study presents, validates, and demonstrates the broad clinical applicability of dry wearable MXene HDsEMG arrays (MXtrodes) fabricated from safe and scalable liquid‐phase processing of Ti3C2Tx. The fabrication scheme allows easy customization of array geometry to match subject anatomy, while the gel‐free and minimal skin preparation enhance usability and comfort. The low impedance and high conductivity of the MXtrode arrays allow detection of the activity of large muscle groups at higher quality and spatial resolution than state‐of‐the‐art wireless electromyography  sensors, and in realistic clinical scenarios. To demonstrate the clinical applicability of MXtrodes in the context of neuromuscular diagnostics and rehabilitation, simultaneous HDsEMG and biomechanical mapping of muscle groups across the whole calf during various tasks, ranging from controlled contractions to walking is shown. Finally, the integration of HDsEMG acquired with MXtrodes with a machine learning pipeline and the accurate prediction of the phases of human gait are shown. The results underscore the advantages and translatability of MXene‐based wearable bioelectronics for studying neuromuscular function and disease, as well as for precision rehabilitation. High‐density surface electromyography (HDsEMG) is crucial for monitoring and diagnosis of neuromuscular pathologies. Ti3C2Tx MXene enables gel‐free, low‐cost, wearable high‐density bioelectronic platform for low impedance and user compatible HDsEMG recordings. Clinical application of MXene electrodes is demonstrated by correlating muscle activity to tendon loading biomechanics. This platform will shift rehabilitation away from standardized guidelines toward precision rehabilitation.